AGV Trajectory Control Based on Laser Sensor Navigation - Thanh Luan Bui; Phuc Thinh Doan; Soon Sil Park; Hak Kyeong Kim; Sang Bong Kim (International Journal of Science and Engineering, 2013)
Autonomous Guided Vehicle Systems (AGVs) are used to transport goods and products in manufacturing fields where navigation can be done in a structured environment. In order to track the given trajectory, a tracking control based on Lyapunov stability theory is introduced. The use of the nonlinear Lyapunov technique provides robustness for load disturbance and sensor noise. To apply Lyapunov's theorem, the kinematic model of AGV is given. To recognize its position in indoor environment, in this paper, a laser sensor device NAV200 is used to detect the AGV position in real-time. For simulation and experiment, software and hardware are described. The AGV consists of 4 wheels with two passive wheels and two driving wheels. A controller is developed based on industrial computer. The effectiveness of the proposed controller is proved by simulation and experimental results.[AGV Trajectory Control, Laser Sensor Navigation]